Vegetation biomass and soil moisture coregulate bacterial community succession under altered precipitation regimes in a desert steppe in northwestern China. (September 2019) - Na, Xiaofan; Yu, Hailong; Wang, Pan; Zhu, Wanwan; Niu, Yubin; Huang, Juying
Abstract: Given that soil water availability is the major limitation on plant growth in desert steppes, uncovering the connections between belowground and aboveground communities under altered precipitation regimes will improve our knowledge of the potential impacts of global climate change on this fragile ecosystem and the services it provides. To investigate the relationships and the underlying drivers of soil bacterial community structure, we established a three-year field experiment in a desert steppe in northwestern China with manipulative precipitation treatments consisting of natural precipitation, 30% reduction, and 30% and 50% increases in precipitation. Results showed that bacterial community composition varied significantly with altered precipitation regimes, but community richness and evenness did not. The bacterial community structure showed much more sensitivity to the increase in precipitation than it did to decrease in precipitation. The effects of altered precipitation regimes on bacterial community composition depended upon the relationship between precipitation, vegetation, and soil properties. Soil microbial biomass C was the best predictor of bacterial community succession when precipitation was experimentally altered. Our results indicated that bacterial communities in desert steppe soils responded to changes in precipitation primarily through plant–soil–microbe interactions, as opposed to responding directly to changes in soil moisture. Highlights: 1. Structure but not diversity of bacterial community varies with altered precipitation. 2. MBC concentration is the best predictor of bacterial community succession. 3. Bacterial community is sensitive to increased precipitation than decreased one. 4. Altered precipitation affects bacterial structure by plant vegetation and soil properties.